Analiza kooperacji bankowo-ubezpieczeniowej w ramach umowy o współpracy w wyodrębnionej dziedzinie - Swacha-Lech, Magdalena (Bank-insurance cooperation analysis within the confines of agreement of cooperation in separated field, 2007)
The aim of article is the presentation of banks-insurance links realized within the confines of two objected forms: co-promotion and distribution agreements occurred on Polish market at the end of 2005. On the basis of research which was carried out for the author it was stated that only seven Imm all banks used co-promotion agreements. More popular was distribution agreements where products which enable tax advantages predominate.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1186, s. 109-121